PENGARUH KEBERADAAN BENDUNGAN LEUWIKERIS DAN BENDUNGAN MATENGGENG TERHADAP ALOKASI AIR DAERAH ALIRAN SUNGAI (DAS) CITANDUY - Alaniri, Yusanuari; Suryadi, Yadi (JURNAL SUMBER DAYA AIR, 2023)
The Citanduy watershed service area, which is located in Cilacap Regency, Ciamis Regency, Pangandaran Regency and Banjar City, is currently experiencing an increase in population growth, residential facilities, and the number of immigrants, so that the demand for raw water in these areas is increasing. On the other hand, the availability of water in the area is decreasing, so it is necessary to study potential sources of raw water to determine the solutions to be taken in order to meet the demand for raw water supply and develop potential water resources in the study area. The purpose of this study is to simulate water allocation using the WEAP (Water Evaluation And Planning) software in the Citanduy watershed area. In the data analysis section, two water balance simulation scenarios were created based on the various suggestions to be recommended for developing the potential of water resources in the study area. From the two scenarios that were implemented, a recommendation emerged to build a new irrigation area of 18.800 ha, the Leuwikeris Reservoir with a volume of 69,56 million m3 and the Matenggeng Reservoir with a volume of 500 million m3. With the plan to meet these water needs, it is necessary to conduct a feasibility study of water allocation in order to find out how technically feasible both the Citanduy River and the Leuwikeris Dam are in meeting the water needs as previously planned. Given the strategic location of West Java and Central Java Provinces and the many irrigation areas located within them, the need for and demand for water services will continue to increase over time.Keywords : simulation of water allocation, Citanduy watershed, Leuwikeris reservoir, Matenggeng reservoir.